UJI AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL UMBI LOBAK PUTIH (Raphanus sativus L.) TERHADAP LIMA BAKTERI PATOGEN DENGAN METODA DIFUSI - emma susanti (Jurnal Penelitian Farmasi Indonesia, 2015)
Antibacterial activity test of white radish tuber extract (Raphanus sativus L.) with a diffusion method was tested against five bacterial pathogens.Thepurpose of this study is to evaluate inhibitory in Gram-negative bacteria (Salmonella thypi, Shigella sonnei, and Escherichia coli) and Gram-positivebacteria (Staphylococcus aureus and Bacillus cereus) at concentrations of 20%, 40%, 60%, 80% and 100%. The results of White Radish tuber extractshowed zone of inhibition against all of bacteria test and provide better inhibition against Gram-negative bacteria at concentrations of 80% and 100%with inhibition diameter of Salmonella thypi bacteria (11,53mm, 11,06mm), Shigella sonnei (11,86mm, 12,33mm) and Escherichia coli (12,76mm,13,53mm). ANOVA analysis showed the influence of the white radish tuber extract concentration against all bacteria tested by a significant value P<0.05.